Aerobic Copper Catalysis for Tandem Oxy‐N‐alkenylation of [1, 2, 3]Triazolo[1, 5‐a]pyridines. Issue 19 (25th August 2016) - Pankajakshan, Sreekumar; Ang, Wei Li; Sreejith, Sivarampanicker; Stuparu, Mihaiela Corina; Loh, Teck‐Peng
Abstract: N ‐Alkenylated triazolinone ylides were generated through copper‐catalyzed oxy‐ N ‐alkenylation of triazolopyridines. The mechanistic course of this aerobic tandem reaction has been experimentally elucidated and primary photophysical data of the ylide products are also given. Abstract :